2014
DOI: 10.1002/eji.201343629
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic acids reduce Th17 differentiation via blockade of IL‐1β‐mediated IRAK1 signaling

Abstract: Interferon-gamma producing CD4+ T (Th1) cells and IL-17-producing CD4 + T (Th17) cells are involved in the pathogenesis of several autoimmune diseases including multiple sclerosis. Therefore, the development of treatment strategies controlling the generation and expansion of these effector cells is of high interest. Frankincense, the resin from trees of the genus Boswellia, and particularly its prominent bioactive compound acetyl-11-keto-β-boswellic acid (AKBA), have potent anti-inflammatory properties. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…While MS is a complex and heterogeneous immunological disease, there is consensus about the importance of a dysregulation of proinflammatory and anti-inflammatory T cell subsets 29. Immunological outcome data from the present trial imply a distinct immunological signature change in the T cell compartment and more specifically in the CD3+ Treg/TH17 subset, which is consistent with our in vitro observations 10. The data of this previous trial focused on CD4+ T cells, the results of the present study indicate that the immunomodulatory effects of SFE are, at least partly, due to reduced IL-17 production of CD8+ T cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While MS is a complex and heterogeneous immunological disease, there is consensus about the importance of a dysregulation of proinflammatory and anti-inflammatory T cell subsets 29. Immunological outcome data from the present trial imply a distinct immunological signature change in the T cell compartment and more specifically in the CD3+ Treg/TH17 subset, which is consistent with our in vitro observations 10. The data of this previous trial focused on CD4+ T cells, the results of the present study indicate that the immunomodulatory effects of SFE are, at least partly, due to reduced IL-17 production of CD8+ T cells.…”
Section: Discussionsupporting
confidence: 89%
“…Diverse immunomodulatory mechanisms have been attributed to BAs, most prominent of which are the inhibition of the enzymes 5-lipoxygenase, microsomal prostaglandin E2 synthase-1, LL-37 and the inhibition of nuclear factor-κB activities 7–9. Previous data from our group showed that BAs interfere with CD4+ T helper cell 17 polarisation by blocking interleukin (IL)-1β signalling in vitro 10. Since involvement of several of the molecules and pathways mentioned above has been reported in the context of MS pathology,11–13 we reasoned that it would be worthwhile to assess the use of a standardised frankincense extract (SFE) as an anti-inflammatory and immunomodulatory therapeutic approach in patients with MS.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-146a was originally described as being significantly up-regulated after microbial endotoxin, lipopolysaccharide or cytokine stimulation of myeloid cells and under transcriptional control by NF-κB; shortly thereafter this inducible miRNA-146a was found to be up-regulated by metal sulfate-generated reactive oxygen species, by pro-inflammatory cytokines (such as IL-1β and TNFα) and by Aβ42 peptides in human primary brain cells (Taganov et al, 2006 ; Lukiw et al, 2008 ; Hill et al, 2009 ; Pogue et al, 2009 ; Cui et al, 2010 ). Further, miRNA-146a targets the 3′-UTR of mRNAs encoding signaling proteins involved in the innate immune and inflammatory response, including complement factor H (CFH) and IRAK-1, and both compartmentalized CFH and IRAK-1 deficiencies are observed in MS (Taganov et al, 2006 ; Cui et al, 2010 ; Ingram et al, 2014 ; Stürner et al, 2014 ). Interestingly, significant amounts of miRNA-146a have been found in glial cells responsible for axonal myelination (Li et al, 2011 ; Alexandrov et al, 2014 ; Kroesen et al, 2015 ).…”
Section: Mirna-146a and Inflammatory Degenerationmentioning
confidence: 99%
“…Interestingly, in experimental autoimmune encephalomyelitis (EAE), a mouse model for MS, miRNA-155 expression has been shown to increase significantly in the spleen, lymph node and brain as EAE progresses, and miRNA-155(–/–) mice exhibit resistance to EAE and significantly less CNS inflammation (Murugaiyan et al, 2011 ; Thamilarasan et al, 2012 ). Both miRNA-146a (see above) and/or miRNA-155: (i) target the CD47 3′-UTR, promoting down-regulation of CD47 on brain resident cells, triggering the macrophage-mediated phagocytosis of myelin (Junker et al, 2009 ) and/or (ii) induce the development of IFN-γ-producing T helper type 1 (Th1) cell subsets and CD4(+) T cells that secrete interleukin (IL)-17 (Th17 cells); these cells are known to induce inflammatory degeneration in MS, psoriasis, autoimmune uveitis and rheumatoid arthritis (Ma et al, 2014 ; Seddiki et al, 2014 ; Stürner et al, 2014 ). Very recently it has been shown that (i) suppressing miRNA-155 expression inhibits the development of Th1 and Th17 cells, resulting in the decrease of disease severity in EAE (Zhang et al, 2014 ); and (ii) anti-miRNA-155 treatment in EAE significantly inhibits EAE development (Murugaiyan et al, 2011 ; Ma et al, 2014 ; Seddiki et al, 2014 ).…”
Section: Mirna-155 and Neurodegenerative Diseasementioning
confidence: 99%
“…The deletion of miR-146a in Tregs may increase the production of IFN- γ and develop severe Th1-mediate lesions [ 24 ]. Further, miRNA-146a was reported to modulate the signaling proteins involved in the innate immune and inflammatory response, such as complement factor H (CFH) and IRAK-1, and both of them were deficient in MS [ 25 28 ].…”
Section: Mirnas Involved In Periphery Inflammationmentioning
confidence: 99%